Changes in Class Structures after the Great Recession: Estonia and Lithuania Compared - Morkevičius, Vaidas; Žvaliauskas, Giedrius; Ambrulevičiūtė, Aelita; Norkus, Zenonas (Studies of Transition States and Societies, 2020)
In the studies of transition states and societies, Estonia and Lithuania are considered as twin cases of the neoliberal Baltic model due to similarities in their political economies and macroeconomic policies. Do similarities between the two countries extend to their class structures? We compare changes of the class composition in Estonia and Lithuania during the 2008-2015 period, encompassing the Great Recession and subsequent recovery. For empirical analysis, we use the European Social Survey (ESS) data and employ the framework of the European Socio-economic Classification (ESeC). We find that by 2015 the class structure of the Estonian society became similar to the class structures in the technologically most advanced post-industrial countries. Changes in the class structure of Lithuania diverged from general trends, preserving many features characteristic of industrial societies.